Factors associated to nipple trauma in lactation period: a systematic review - Janaína Silva Dias; Tatiana de Oliveira Vieira; Graciete Oliveira Vieira
Abstract Objectives: To identify the characteristics associated to nipple trauma in nursing mothers and propose a theoretical model explaining in hierarchical levels its determining factors. Methods: a systematic review of the literature based on the search of epidemiological studies of factors associated to nipple trauma in the databases of Medical Literature Analysis and Retrieval System Online/Pubmed, Literatura Latino-Americana and Caribe em Ciências da Saúde (Latin American Literature and Caribbean Health Sciences) and ScienceDirect. The conduct on searching articles occurred until June 2016. Results: 17 articles were selected which investigated 27 variables and found a significant association between 16 of these variables and nipple trauma. The factors associated to nipple trauma reported in two or more studies were: mother of race/color white or yellow, primiparity, inadequate position between mother and child during breastfeeding and handling the infant incorrectly to the mother's breast. Guidance received on handling and positioning the infant during prenatal care was a protective factor against nipple trauma. Conclusions: in the theoretical model explaining the factors associated to nipple trauma in hierarchical levels, the variables classified at the proximal level were the most investigated and were identified as risk factors in selected studies, indicating that in the postpartum care period is an important protective factor against nipple trauma.